1998
DOI: 10.2739/kurumemedj.45.227
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal Varices as a Cause of Massive Gastrointestinal Bleeding. A Case Report.

Abstract: This report describes a 49-year-old woman with recurrent massive gastrointestinal bleeding from jejunal varices without portal hypertension. Preoperative diagnosis was obtained by abdominal computed tomography, superior mesenteric arterial angiography and percutaneous transhepatic portography. Percutaneous transhepatic portographic findings revealed no step-up of oxygen concentration and normal pressure in the portal vein, only dilation of superior mesenteric vein. Jejunal resection and anastomosis resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Most patients with this condition who experience sudden hematochezia undergo emergency surgery, and the postoperative mortality rate remains high since accurate preoperative diagnosis is often diffi cult. 5,6 An accurate preoperative diagnosis is important for the safe performance of the operation. On the other hand, about 11% of patients with obscure gastrointestinal bleeding are not detected by capsule endoscopy, 7 and the limitations of capsule endoscopy in emergency situations of obscure gastrointestinal bleeding must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with this condition who experience sudden hematochezia undergo emergency surgery, and the postoperative mortality rate remains high since accurate preoperative diagnosis is often diffi cult. 5,6 An accurate preoperative diagnosis is important for the safe performance of the operation. On the other hand, about 11% of patients with obscure gastrointestinal bleeding are not detected by capsule endoscopy, 7 and the limitations of capsule endoscopy in emergency situations of obscure gastrointestinal bleeding must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated jejunal varices are a rare vascular cause of massive gastrointestinal haemorrhage usually described in the setting of portal hypertension (PHT) 1 . We report a very rare case of bleeding isolated jejunal varices in the absence of PHT, which was treated by surgical excision.…”
mentioning
confidence: 97%
“…We report a very rare case of bleeding isolated jejunal varices in the absence of PHT, which was treated by surgical excision. A review of available published work has shown only two such cases reported previously 1,2 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few cases in the literature of patients without portal hypertension who had duodenal or jejunal varices that resulted in GITB [3,4].…”
Section: Introductionmentioning
confidence: 99%